Unveiling Functional Impairment in Fabry Disease: The Role of Peripheral vs. Cardiac Mechanisms - Geza Halasz; Chiara Lanzillo; Raffaella Mistrulli; Emanuele Canali; Elisa Fedele; Paolo Ciacci; Federica Onorato; Guido Giacalone; Giovanni Nardecchia; Domenico Gabrielli; Federica Re (Biomedicines, 2025)
Background: Anderson–Fabry disease (AFD) is a progressive lysosomal storage disorder characterized by systemic glycosphingolipid accumulation. While cardiac imaging plays a central role in disease monitoring, the relationship between structural myocardial changes and exercise capacity remains incompletely defined. This study aimed to evaluate functional impairment in AFD patients using cardiopulmonary exercise testing (CPET) and to determine whether limitations are primarily cardiac or extracardiac in origin. Methods: Thirty-one patients with genetically confirmed AFD were retrospectively enrolled from two tertiary centers. All underwent baseline clinical assessment, resting transthoracic echocardiography (TTE), spirometry, and symptom-limited CPET using a cycle ergometer and a 10 W/min ramp protocol. Echocardiographic parameters included the LVEF, global longitudinal strain (GLS), E/e′ ratio, TAPSE, and PASP. CPET measurements included the peak VO2, anaerobic threshold (AT), VE/VCO2 slope, oxygen pulse (VO2/HR), and VO2/watt ratio. Results: The mean age was 48.4 ± 17.6 years, with most patients classified as NYHA I. LVEF was preserved (62.3 ± 8.6%), and diastolic indices were within normal limits (E/e′ 7.1 ± 2.4), but GLS was impaired (11.3 ± 10.5%). CPET showed reduced peak VO2 (18.6 ± 6.1 mL/kg/min; 71.4% predicted) and early AT (40.8%), with preserved ventilatory efficiency and oxygen pulse. VO2/watt was mildly reduced, suggesting peripheral limitations despite intact central hemodynamics. Conclusions: Functional impairment is common in AFD patients, even with mild cardiac involvement. CPET reveals early systemic limitations not captured by standard imaging, supporting its role in phenotypic characterization and therapeutic decision-making.